1999
DOI: 10.1212/wnl.52.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine autoreceptor function is lost in advanced Parkinson’s disease

Abstract: We suggest that in mild and stable PD an upregulated presynaptic inhibitory feedback regulation, particularly in the dorsal putamen, acts to maintain congruity within the dopaminergic system in response to antiparkinsonian medication. However, this inhibitory feedback regulation is diminished with the progression of nigrostriatal degeneration and chronic dopamine agonist treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…One hypothesis is that they are primarily caused by postsynaptic alterations in receptor density or sensitivity (Bravi et al, 1994;Verhagen Metman et al, 1997;Zigmond et al, 1990). However, some recent studies suggest that changes in presynaptic autoregulatory function may accompany disease progression and that these changes may contribute to the development of altered therapeutic response (Ekesbo et al, 1999;Tedroff et al, 1996). These studies were based on the idea that dopamine synthesis, storage, and release are "autoregulated" in such a way as to maintain the synaptic concentration of dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis is that they are primarily caused by postsynaptic alterations in receptor density or sensitivity (Bravi et al, 1994;Verhagen Metman et al, 1997;Zigmond et al, 1990). However, some recent studies suggest that changes in presynaptic autoregulatory function may accompany disease progression and that these changes may contribute to the development of altered therapeutic response (Ekesbo et al, 1999;Tedroff et al, 1996). These studies were based on the idea that dopamine synthesis, storage, and release are "autoregulated" in such a way as to maintain the synaptic concentration of dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Ekesbo et al (1999) found that although patients with early PD were able to downregulate the uptake of L-[ 11 C]-dopa in response to apomorphine challenge, this ability was lost in patients with more advanced disease. Based on these findings, they proposed that there might be a loss of autoreceptor function with the progression of PD.…”
mentioning
confidence: 99%
“…Acute administration of dopamine antagonists rarely causes acute parkinsonism in humans (8) and fails to cause parkinsonian electrophysiological abnormalities in animals (9,10). While striatal changes related to the dopaminergic denervation are undoubtedly prominent in PD (11)(12)(13)(14)(15), it remains unclear whether this pathology alone is sufficient to cause the parkinsonian hypokinetic movements. In addition to the direct and indirect pathways in the cortico-basal ganglia circuitry, there is a relatively neglected cortico-subthalamic (or "hyperdirect") pathway that bypasses the striatum and sends cortical commands directly to the subthalamic nucleus (STN) (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…2 It is difficult to understand, however, how such a putative mechanism could be relevant in animals and patients who have lost approximately 95% of their nigrostriatal terminals. 22 In addition, we have found that the sensitivity of dopamine neurons to apomorphine remained unaltered by denervation and levodopa treatment. 23 4.…”
mentioning
confidence: 89%